Synthesis and Biological Evaluation of 2-(3-Methyl-2-oxoquinoxalin-1(2H)-yl)-N'-(substituted phenyl-methyledene/ethylidene)acetohydrazides - Gopal Krishna Rao; R. B. Kotnal; P. N. Sanjay Pai (E-Journal of Chemistry)
A series of quinoxaline derivatives was prepared and evaluated for antitubercular, antibacterial and antifungal activities. The title compounds were prepared by condensation of substituted aromatic aldehydes and substituted acetophenones with 2-(3-methyl-2-oxoquinoxalin-1(2H)-yl) acetohydrazide. Structures of all these compounds were confirmed by their spectral studies. Among synthesized compounds (4r, 4t, 4u, 4w and 4x) have shown good anti tubercular activity (25 µg mL-1) when compared to reference drugs pyrazinamide (10 µg mL-1) and streptomycin (7.5 µg mL-1). In this study, few derivatives showed broad spectrum of antimicrobial activity at low concentration. The MICs (Minimum inhibitory concentration) of some compounds are 2-4 µg mL-1.